Composite electrolyte membrane and preparation method and application thereof

By using lithium salt, oxide electrolyte and polymer in the composite electrolyte membrane and using a pressurized molding process, the problems of solvent use and mechanical properties during the preparation of composite electrolyte membrane in the prior art are solved, and a high-performance thin flexible electrolyte membrane is achieved.

CN119518071APending Publication Date: 2025-02-25SHENZHEN INX ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310996728.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-08
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing composite electrolyte membrane requires the use of solvents during the preparation process, which is difficult to simultaneously improve the electrolyte content and mechanical properties, and the interface contact with the electrode is poor, making it difficult to meet the requirements of thin flexible films.

Method used

A composite electrolyte membrane containing lithium salt, first oxide electrolyte, second oxide electrolyte, stearic acid, polyethylene oxide and polytetrafluoroethylene is prepared by a pressurized molding process to ensure uniform dispersion of the electrolyte and high ceramic content.

Benefits of technology

The solvent-free preparation process is realized, the conductivity and mechanical properties of the electrolyte membrane are improved, the requirements of thin flexible films are met, and good performance is shown in lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518071A_ABST
    Figure CN119518071A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a composite electrolyte membrane, a preparation method of the composite electrolyte membrane and application of the composite electrolyte membrane in a lithium ion battery. The composite electrolyte membrane comprises a lithium salt, a first oxide electrolyte, a second oxide electrolyte, stearic acid, polyoxyethylene, polytetrafluoroethylene and an optional plasticizer, the D50 of the first oxide electrolyte is 10-200 nm, and the D50 of the second oxide electrolyte is 500-5 [mu] m. According to the invention, the compact and soft composite electrolyte membrane with certain strength can be obtained by using less binder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite electrolyte membrane and a preparation method thereof, as well as application in lithium ion batteries. Background Art

[0002] Diaphragm materials used in lithium-ion batteries generally include polymer electrolytes (such as ceramics and glass), oxide electrolytes, etc. Although polymer electrolytes have good mechanical flexibility and close contact with electrodes, and are easy to prepare into thin films, they usually have low ionic conductivity at room temperature, insufficient electrochemical stability, and poor fire resistance, which seriously limit their practical applications. Oxide electrolytes have great application potential in high-safety lithium metal batteries due to their non-flammability, high ionic conductivity, wide electrochemical window, and good chemical stability. However, ceramic-type oxide electrolytes have poor interfacial contact with electrodes, are usually thick and brittle, and cannot meet the requirements of thin flexible films for practical applications.

[0003] In recent years, polymer-ceramic composite electrolytes have been widely studied and developed, as they not only maintain good flexibility but also have high ionic conductivity. However, existing composite electrolyte membranes usually require a wet preparation method involving solvents, and it is difficult to simultaneously obtain a higher electrolyte content and good mechanical properties. Summary of the invention

[0004] In order to solve the above technical problems, the first aspect of the present invention provides a composite electrolyte membrane, which includes a lithium salt, a first oxide electrolyte, a second oxide electrolyte, stearic acid, optionally polyethylene oxide, optionally polytetrafluoroethylene and optionally a plasticizer;

[0005] Wherein, the D 50 is 10-200nm, the D of the second oxide electrolyte 50 The thickness of the first oxide electrolyte is 500 nm-5 μm, and the weight ratio of the first oxide electrolyte to the second oxide electrolyte is 1:1-3, preferably 1:1.5-2;

[0006] The molecular weight of the polyethylene oxide is 5 million or more.

[0007] In some specific embodiments, the D of the first oxide electrolyte is 50 50-150nm, the D of the second oxide electrolyte 50 600nm-2μm.

[0008] In some specific embodiments, the first oxide electrolyte and the second oxide electrolyte are each independently selected from one or more of lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum titanium oxide, and lithium germanium aluminum phosphate; more preferably, the first oxide electrolyte and the second oxide electrolyte each independently further contain one or more doping elements selected from aluminum, gallium, and tantalum.

[0009] In some specific embodiments, the lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethylsulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB).

[0010] In some specific embodiments, the molecular weight of the polyethylene oxide is 6 million to 8 million.

[0011] In some specific embodiments, the polytetrafluoroethylene is dispersed polytetrafluoroethylene.

[0012] In some specific embodiments, the total weight of the first oxide electrolyte and the second oxide electrolyte accounts for 50-98%, preferably 60-90%, relative to the total weight of the composite electrolyte membrane.

[0013] In some specific embodiments, the weight of the lithium salt accounts for 1-10%, preferably 2-7%, relative to the total weight of the composite electrolyte membrane.

[0014] In some specific embodiments, relative to the total weight of the composite electrolyte membrane, the weight of stearic acid is 0.1-2%, preferably 0.2-1%; and / or the weight of polyethylene oxide is 0-10%, preferably 1-10%, more preferably 2-6%; and / or the weight of polytetrafluoroethylene is 0-5%, preferably 0.1-5%, more preferably 0.2-1%.

[0015] A second aspect of the present invention provides a method for preparing a composite electrolyte membrane, the method comprising: press-forming an electrolyte mixture to obtain a composite electrolyte membrane;

[0016] The electrolyte mixture contains a lithium salt, a first oxide electrolyte, a second oxide electrolyte, stearic acid, optionally polyethylene oxide, optionally polytetrafluoroethylene, and optionally a plasticizer;

[0017] The D of the first oxide electrolyte 50The second oxide electrolyte has a D of 10-200 nm. 50 The thickness of the first oxide electrolyte is 500 nm-5 μm, and the weight ratio of the first oxide electrolyte to the second oxide electrolyte is 1:1-3, preferably 1:1.5-2;

[0018] The molecular weight of the polyethylene oxide is 5 million or more.

[0019] In some specific embodiments, the D of the first oxide electrolyte is 50 50-150nm, the D of the second oxide electrolyte 50 600nm-2μm.

[0020] In some specific embodiments, the first oxide electrolyte and the second oxide electrolyte are each independently selected from one or more of lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum titanium oxide, and lithium germanium aluminum phosphate; more preferably, the first oxide electrolyte and the second oxide electrolyte each independently further contain one or more doping elements selected from aluminum, gallium, and tantalum.

[0021] In some specific embodiments, the lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethylsulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB).

[0022] In some specific embodiments, the molecular weight of the polyethylene oxide is 6-8 million.

[0023] In some specific embodiments, the polytetrafluoroethylene is dispersed polytetrafluoroethylene.

[0024] In some specific embodiments, the total weight of the first oxide electrolyte and the second oxide electrolyte accounts for 50-98%, preferably 60-90%, relative to the total weight of the electrolyte mixture.

[0025] In some specific embodiments, the weight of the lithium salt accounts for 1-10%, preferably 2-7%, relative to the total weight of the electrolyte mixture.

[0026] In some specific embodiments, relative to the total weight of the electrolyte mixture, the weight of stearic acid is 0.1-2%, preferably 0.2-1%; and / or the weight of polyethylene oxide is 0-10%, preferably 1-10%, more preferably 2-6%; and / or the weight of polytetrafluoroethylene is 0-5%, preferably 0.1-5%, more preferably 0.2-1%.

[0027] In some specific embodiments, the method for preparing the electrolyte mixture comprises the following steps:

[0028] (1) performing a first mixing of a first oxide electrolyte, a second oxide electrolyte, and stearic acid to obtain a first mixture;

[0029] (2) mixing the first mixture obtained in step (1) with a lithium salt and an optional plasticizer to obtain a second mixture;

[0030] (3) performing a third mixing of the second mixture obtained in step (2) and optional polyethylene oxide to obtain a third mixture;

[0031] (4) Optionally, the third mixture obtained in step (3) is mixed with polytetrafluoroethylene to obtain a fourth mixture.

[0032] In some specific embodiments, the first mixing to the fourth mixing are all performed by grinding.

[0033] In some specific embodiments, the grinding conditions include: a rotation speed of 5000 rpm or more, preferably 6000-10000 rpm; and a time of 2 min or more, preferably 2-10 min.

[0034] In some specific embodiments, the conditions for the pressurization molding include: a temperature of 20-80°C, preferably 50-80°C.

[0035] The third aspect of the present invention provides the use of the composite electrolyte membrane of the present invention or the composite electrolyte membrane prepared by the preparation method of the present invention in a lithium ion battery.

[0036] Advantageous Effects of the Invention

[0037] Stearic acid (SA) is widely used in plastics and rubber as a lubricant, dispersant, surface modifier, etc. In the present invention, the inventor creatively applies SA to the preparation of composite solid electrolytes. The melted SA is evenly coated on the surface of the oxide electrolyte powder at high temperature, which has a very excellent improvement effect on the processing and final performance of the electrolyte membrane. On the one hand, SA can react with the lithium carbonate on the surface of the oxide electrolyte, thereby removing the inert lithium carbonate layer, and the generated lithium stearate can not only participate in the transportation of lithium ions but also have good compatibility with PEO, promoting the rapid transmission of lithium ions at the two-phase interface. On the other hand, SA plays the role of a lubricant and a dispersant. The oxide electrolyte can be very evenly dispersed in PEO, improving the consistency of the electrolyte membrane and promoting the uniform transmission of lithium ions.

[0038] Dispersed PTFE can be fibrous under shear force to form a mesh, which is very suitable for the preparation of high ceramic content membranes. Ultra-high molecular weight PEO has very high viscoelasticity, which can give the electrolyte membrane good flexibility. The present invention further uses ultra-high molecular weight PEO as the main polymer binder and trace PTFE as the auxiliary binder to obtain a high ceramic content electrolyte membrane with good strength and flexibility.

[0039] The composite electrolyte membrane of the present invention can achieve the following technical effects through its appropriate composition.

[0040] (1) SA improves the interface contact between oxide powder and PEO; it can be used as a dispersant to promote the uniform dispersion of oxide powder in PEO; it can be used as a lubricant to improve the fluidity of the membrane, facilitate processing, and obtain an electrolyte membrane with a smooth surface.

[0041] (2) The use of different oxide powder sizes is conducive to powder accumulation. With a higher content of oxide powder, a dense, soft, and strong electrolyte membrane can be obtained by using less binder.

[0042] (3) Dry membrane preparation: by using ultra-high molecular weight PEO and PTFE together, no solvent is used, the process is simple, the efficiency is high, and continuous production is possible. Ultra-high molecular weight PEO has a large bonding force and can provide strong surface bonding. Under the action of shear force, PTFE becomes fibrous and can provide more mesh bonding. The double bonding of the surface and the mesh gives the electrolyte membrane a high ceramic content while having good flexibility and mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 A schematic structural diagram of the composite electrolyte membrane of the present invention is shown. DETAILED DESCRIPTION

[0044] The present invention is further described below by means of specific embodiments. Unless otherwise specified, the academic terms used herein have the same meanings as those generally understood by those of ordinary skill in the art.

[0045] Numerical limits or ranges stated herein are inclusive of the endpoints and specifically include all values ​​and sub-ranges within the numerical limits or ranges.

[0046] The term "optional" herein means that the corresponding component may or may not be included.

[0047] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.

[0048] In the present invention, D 50 It indicates the particle size corresponding to when the cumulative particle size distribution percentage of the sample reaches 50%, sometimes also referred to as "particle size" for short; molecular weight is the number average molecular weight.

[0049] A first aspect of the present invention provides a composite electrolyte membrane, the composite electrolyte membrane comprising a lithium salt, a first oxide electrolyte, a second oxide electrolyte, stearic acid (SA), optionally polyethylene oxide (PEO), optionally polytetrafluoroethylene (PTFE) and optionally a plasticizer;

[0050] Wherein, the D 50 is 10-200nm, the D of the second oxide electrolyte 50 The thickness of the first oxide electrolyte is 500 nm-5 μm, and the weight ratio of the first oxide electrolyte to the second oxide electrolyte is 1:1-3;

[0051] The molecular weight of the polyethylene oxide is 5 million or more.

[0052] like Figure 1 As shown in the structural schematic diagram, in the composite electrolyte membrane of the present invention, the black area shows PEO, the large gray balls show large particles of the first oxide electrolyte powder, the small gray balls show small particles of the second oxide electrolyte powder, the white dotted line on the surface of the electrolyte powder represents the SA coated on the surface of the oxide electrolyte powder, and the white fiber thread represents the fiberized PTFE. By selecting the above-mentioned composite electrolyte membrane composition of the present invention, the following can be obtained: Figure 1 The membrane structure shown.

[0053] In a preferred embodiment of the present invention, the composite electrolyte membrane comprises a lithium salt, a first oxide electrolyte, a second oxide electrolyte, stearic acid (SA), polyethylene oxide (PEO), polytetrafluoroethylene (PTFE) and an optional plasticizer. In a more preferred embodiment of the present invention, the composite electrolyte membrane comprises a lithium salt, a first oxide electrolyte, a second oxide electrolyte, stearic acid (SA), polyethylene oxide (PEO), polytetrafluoroethylene (PTFE) and a plasticizer.

[0054] In the present invention, the first oxide electrolyte and the second oxide electrolyte are each independently selected from lithium lanthanum zirconium oxide (LLZO, i.e. Li7La3Zr2O 12 ), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum titanate oxide (LLTO), lithium aluminum germanium phosphate (LAGP), which may be the same or different, preferably lithium lanthanum zirconium oxide. Furthermore, the first oxide electrolyte and the second oxide electrolyte may each independently contain one or more doping elements selected from aluminum, gallium, and tantalum. According to some specific embodiments of the present invention, the first oxide electrolyte and / or the second oxide electrolyte may be aluminum-doped lithium lanthanum zirconium oxide (LALZO, Li (7-x) Al (x) Ln3Z (2-x) O 12 , where x can be 0.01-0.8)

[0055] Preferably, the D of the first oxide electrolyte is 50 is 50-200nm, more preferably 50-150nm; D of the second oxide electrolyte 50 In addition, the D 50 For example, it can be 10 nm, 30 nm, 50 nm, 70 nm, 90 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm or 200 nm, etc.; and / or D of the second oxide electrolyte 50 For example, it may be 500 nm, 700 nm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.

[0056] In the present invention, the lithium salt may be any lithium salt commonly used in lithium ion batteries, for example, it may be selected from one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB), among which lithium bis(trifluoromethanesulfonyl)imide is preferred.

[0057] In the present invention, the plasticizer may be, for example, one or more of succinonitrile (SN), polyethylene glycol, and dioctyl phthalate, among which succinonitrile is preferred.

[0058] In order to achieve good film-forming properties, the polytetrafluoroethylene is a dispersed polytetrafluoroethylene. In the present invention, dispersed polytetrafluoroethylene refers to polytetrafluoroethylene with good fiber-forming properties. Such polytetrafluoroethylene molecules are electrically neutral, the cohesion between particles is low, and the molecular chains are arranged along the long axis direction of the particles when subjected to a small shearing effect, and can form linear fibers.

[0059] According to a preferred embodiment of the present invention, the molecular weight of the polyethylene oxide is 5 million to 10 million, preferably 6 million to 8 million. By selecting polyethylene oxide with the above molecular weight, a composite electrolyte membrane with better performance can be obtained. In addition, the molecular weight of the polyethylene oxide can be 5 million, 6 million, 7 million or 8 million, etc.

[0060] In the present invention, the weight ratio of the first oxide electrolyte to the second oxide electrolyte can be, for example, 1:1, 1:1.2, 1:1.4, 1:1.5, 1:1.7, 1:1.9, 1:2, 1:2.2, 1:2.4, 1:2.5, 1:2.7, 1:2.9 or 1:3.

[0061] According to a preferred embodiment of the present invention, from the perspective of further improving the flexibility and mechanical strength of the prepared composite electrolyte membrane, preferably, relative to the total weight of the composite electrolyte membrane, the total weight of the first oxide electrolyte and the second oxide electrolyte accounts for 50-98%, preferably 60-90%. As the total weight ratio of the first oxide electrolyte and the second oxide electrolyte, for example, it can be 50%, 60%, 70%, 80%, 90%, 95% or 98%.

[0062] According to a preferred embodiment of the present invention, the weight of the lithium salt is 1-10%, preferably 2-7%, relative to the total weight of the composite electrolyte membrane. The weight proportion of the lithium salt may be, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0063] According to a preferred embodiment of the present invention, from the perspective of further improving the flexibility and mechanical strength of the prepared composite electrolyte membrane, the content of each component can be selected as follows. Relative to the total weight of the composite electrolyte membrane, the weight of stearic acid accounts for 0.1-2%, preferably 0.2-1%, and more preferably 0.4-0.8%. Relative to the total weight of the composite electrolyte membrane, the weight of polyethylene oxide accounts for 0-10%, preferably 1-10%, more preferably 2-6%, and further preferably 3-5%. Relative to the total weight of the composite electrolyte membrane, the weight of polytetrafluoroethylene accounts for 0-5%, preferably 0.1-5%, more preferably 0.2-1%, and further preferably 0.4-0.6%. In addition, the weight of the plasticizer can account for 1-15%, preferably 5-10%.

[0064] According to the present invention, preferably, the ionic conductivity of the composite electrolyte membrane is 0.1 mS / cm or more, preferably 0.15 mS / cm or more, 0.2 mS / cm or more, or 0.3 mS / cm or more. Specifically, the ionic conductivity of the composite electrolyte membrane may be, for example, 0.1-0.7 mS / cm.

[0065] According to the present invention, preferably, the tensile strength of the composite electrolyte membrane is greater than 3 MPa, for example, 3-10 MPa; in addition, the elongation may be greater than 5%, for example, 5-10%.

[0066] A second aspect of the present invention provides a method for preparing a composite electrolyte membrane, the method comprising: press-forming an electrolyte mixture to obtain a composite electrolyte membrane;

[0067] The electrolyte mixture contains a lithium salt, a first oxide electrolyte, a second oxide electrolyte, stearic acid, optionally polyethylene oxide, optionally polytetrafluoroethylene, and optionally a plasticizer;

[0068] The D of the first oxide electrolyte 50 The second oxide electrolyte has a D of 10-200 nm. 50 The thickness of the first oxide electrolyte is 500 nm-5 μm, and the weight ratio of the first oxide electrolyte to the second oxide electrolyte is 1:1-3;

[0069] The molecular weight of the polyethylene oxide is 5 million or more.

[0070] In a preferred embodiment of the present invention, the electrolyte mixture contains a lithium salt, a first oxide electrolyte, a second oxide electrolyte, stearic acid (SA), polyethylene oxide (PEO), polytetrafluoroethylene (PTFE) and an optional plasticizer. In a more preferred embodiment of the present invention, the electrolyte mixture contains a lithium salt, a first oxide electrolyte, a second oxide electrolyte, stearic acid (SA), polyethylene oxide (PEO), polytetrafluoroethylene (PTFE) and a plasticizer.

[0071] In the present invention, the first oxide electrolyte and the second oxide electrolyte are each independently selected from one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum titanium oxide (LLTO), and lithium aluminum germanium phosphate (LAGP). Furthermore, the first oxide electrolyte and the second oxide electrolyte may each independently contain one or more doping elements selected from aluminum, gallium, and tantalum. According to some preferred embodiments of the present invention, the first oxide electrolyte and / or the second oxide electrolyte may be aluminum-doped lithium lanthanum zirconium oxide (LALZO, Li (7-x) Al (x) Ln3Z (2-x) O 12 , where x can be 0.01-0.8)

[0072] Preferably, the D of the first oxide electrolyte is 50 is 50-200nm, more preferably 50-150nm; D of the second oxide electrolyte 50 In addition, the D 50 For example, it can be 10 nm, 30 nm, 50 nm, 70 nm, 90 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm or 200 nm, etc.; and / or D of the second oxide electrolyte 50 For example, it may be 500 nm, 700 nm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.

[0073] In the present invention, the lithium salt may be any lithium salt commonly used in lithium ion batteries, for example, it may be selected from one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB), among which lithium bis(trifluoromethanesulfonyl)imide is preferred.

[0074] In the present invention, the plasticizer may be, for example, one or more of succinonitrile (SN), polyethylene glycol, and dioctyl phthalate, among which succinonitrile is preferred.

[0075] In order to achieve good dispersibility, the polytetrafluoroethylene is a dispersible polytetrafluoroethylene. In the present invention, the dispersible polytetrafluoroethylene refers to a polytetrafluoroethylene with good fiber-forming properties. Such polytetrafluoroethylene molecules are electrically neutral, the cohesion between particles is low, and the molecular chains are arranged along the long axis direction of the particles when subjected to a small shearing effect, and can form linear fibers.

[0076] According to a preferred embodiment of the present invention, the molecular weight of the polyethylene oxide is 5 million to 10 million, preferably 6 million to 8 million. By selecting polyethylene oxide with the above molecular weight, a composite electrolyte membrane with better performance can be obtained. In addition, the molecular weight of the polyethylene oxide can be 5 million, 6 million, 7 million or 8 million, etc.

[0077] In the present invention, the weight ratio of the first oxide electrolyte to the second oxide electrolyte can be, for example, 1:1, 1:1.2, 1:1.4, 1:1.5, 1:1.7, 1:1.9, 1:2, 1:2.2, 1:2.4, 1:2.5, 1:2.7, 1:2.9 or 1:3.

[0078] According to a preferred embodiment of the present invention, from the perspective of further improving the flexibility and mechanical strength of the prepared composite electrolyte membrane, preferably, relative to the total weight of the electrolyte mixture, the total weight of the first oxide electrolyte and the second oxide electrolyte accounts for 50-98%, 50-98%, preferably 60-90%. As the total weight ratio of the first oxide electrolyte and the second oxide electrolyte, for example, it can be 50%, 60%, 70%, 80%, 90%, 95% or 98%, etc.

[0079] According to a preferred embodiment of the present invention, the weight of the lithium salt is 1-10%, preferably 2-7%, relative to the total weight of the electrolyte mixture. The weight proportion of the lithium salt may be, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0080] According to a preferred embodiment of the present invention, from the perspective of further improving the flexibility and mechanical strength of the prepared composite electrolyte membrane, the content of each component can be selected as follows. Relative to the total weight of the electrolyte mixture, the weight of stearic acid accounts for 0.1-2%, preferably 0.2-1%, and more preferably 0.4-0.8%. Relative to the total weight of the composite electrolyte membrane, the weight of polyethylene oxide accounts for 0-10%, preferably 1-10%, more preferably 2-6%, and further preferably 3-5%. Relative to the total weight of the composite electrolyte membrane, the weight of polytetrafluoroethylene accounts for 0-5%, preferably 0.1-5%, more preferably 0.2-1%, and further preferably 0.4-0.6%. In addition, the weight of the plasticizer can account for 1-15%, preferably 5-10%.

[0081] In the present invention, the preparation method of the electrolyte mixture is not particularly limited, as long as the lithium salt, the first oxide electrolyte, the second oxide electrolyte, stearic acid, optional polyethylene oxide, optional polytetrafluoroethylene and optional plasticizer can be fully mixed to obtain a mixture. Specifically, the mixing can be carried out in two or more steps, for example, two or more of the above ingredients can be mixed first, and then mixed with the remaining ingredients; or two or more of the above ingredients can be mixed first, and then mixed with other ingredients in sequence.

[0082] As a specific embodiment, the preparation method of the electrolyte mixture comprises the following steps:

[0083] (1) performing a first mixing of a first oxide electrolyte, a second oxide electrolyte, and stearic acid to obtain a first mixture;

[0084] (2) mixing the first mixture obtained in step (1) with a lithium salt and an optional plasticizer to obtain a second mixture;

[0085] (3) performing a third mixing of the second mixture obtained in step (2) and optional polyethylene oxide to obtain a third mixture;

[0086] (4) Optionally, the third mixture obtained in step (3) is mixed with polytetrafluoroethylene to obtain a fourth mixture.

[0087] In order to obtain better mixing efficiency and mixing effect, the first to fourth mixing are all performed by grinding. More preferably, the grinding conditions include: a rotation speed of 5000 rpm or more, preferably 6000-10000 rpm; a time of 2 min or more, preferably 2-10 min.

[0088] In the present invention, a composite electrolyte membrane is prepared by press-molding an electrolyte mixture. The press-molding conditions can be appropriately selected according to the needs of preparing the composite electrolyte membrane. For example, the press-molding conditions may include: a temperature of 20-80° C., preferably 50-80° C. The press-molding may be performed by flat plate press or roller press, using any instrument commonly used in the art for pressing composite electrolyte membranes.

[0089] The third aspect of the present invention provides the use of the composite electrolyte membrane described in the first aspect of the present invention or the composite electrolyte membrane prepared by the preparation method described in the second aspect of the present invention in a lithium ion battery.

[0090] Example

[0091] The experimental methods in the following examples are all conventional methods unless otherwise specified.

[0092] In the following examples and comparative examples, the relevant reagents used are as follows.

[0093]

[0094] In the following examples and comparative examples, the main instruments used are as follows:

[0095] High speed grinder: Liren grinding mill, Liren Electric, MFJ-W317.

[0096] Roller press: Laboratory heated pole piece roller press, Xiamen Tianmeifu Machinery Equipment Co., Ltd., TMAX-JRDG100.

[0097] Example 1

[0098] Weigh 3g of LLZO powder with a particle size of 100nm, 5g of LLZO powder with a particle size of 1μm and 0.05g of SA into a high-speed grinder and grind at 8000rpm for 5min at 70°C. Then add 0.6g of LiTFSI and 0.9g of SN and grind for 5min. Continue to add 0.4g of PEO with a molecular weight of 7.9 million and grind for 5min. Finally, add 0.05g of PTFE and grind for 5min. The final electrolyte mixture is repeatedly rolled on a roller press at 70°C to form a composite electrolyte membrane with a thickness of 20μm.

[0099] Example 2

[0100] A composite electrolyte membrane was prepared according to the method of Example 1, except that the added amount of 100 nm LLZO was 4 g and the added amount of 1 μm LLZO was 4 g.

[0101] Example 3

[0102] A composite electrolyte membrane was prepared according to the method of Example 1, except that the added amount of 100 nm LLZO was 2 g and the added amount of 1 μm LLZO was 6 g.

[0103] Example 4

[0104] A composite electrolyte membrane was prepared according to the method in Example 1 except that PTFE was not added.

[0105] Example 5

[0106] A composite electrolyte membrane was prepared according to the method in Example 1 except that PEO was not added.

[0107] Example 6

[0108] The composite electrolyte membrane was prepared according to the method in Example 1 except that the PEO in Example 1 was replaced with PEO with a molecular weight of 5 million.

[0109] Example 7

[0110] A composite electrolyte membrane was prepared according to the method in Example 1 except that 3 g of LLZO powder with a particle size of 50 nm and 5 g of LLZO powder with a particle size of 2 μm were used.

[0111] Example 8

[0112] A composite electrolyte membrane was prepared according to the method in Example 1 except that 3 g of LLZO powder with a particle size of 200 nm and 5 g of LLZO powder with a particle size of 5 μm were used.

[0113] Example 9

[0114] A composite electrolyte membrane was prepared according to the method in Example 1 except that the amount of SA used was 0.2 g.

[0115] Example 10

[0116] A composite electrolyte membrane was prepared according to the method in Example 1 except that the amount of PTFE used was 0.2 g.

[0117] Comparative Example 1

[0118] A composite electrolyte membrane was prepared according to the method in Example 1 except that SA was not added.

[0119] Comparative Example 2

[0120] A composite electrolyte membrane was prepared according to the method in Example 1, except that all LLZO powders (8 g) with a particle size of 100 nm were used.

[0121] Comparative Example 3

[0122] A composite electrolyte membrane was prepared according to the method in Example 1, except that all LLZO powders (8 g) with a particle size of 1 μm were used.

[0123] Comparative Example 4

[0124] A composite electrolyte membrane was prepared according to the method in Example 1 except that the PEO in Example 1 was replaced with PEO with a molecular weight of 600,000.

[0125] Test Case

[0126] The composite electrolyte membranes obtained in the above examples and comparative examples were subjected to performance tests according to the following method.

[0127] Test method:

[0128] Ionic conductivity: Stainless steel sheets were placed on both sides of the solid electrolyte membrane as blocking electrodes, button cells were assembled, and AC impedance tests were performed using an electrochemical workstation. Appropriate amplitude voltage and frequency were set, and the test results were fitted and calculated to obtain the ionic conductivity.

[0129] The formula for calculating ionic conductivity is: σ = d / (R × S), where σ represents conductivity; R is the impedance value of the electrolyte membrane obtained by the test, in Ω; S is the electrode area, in cm 2 ; d is the thickness of the electrolyte membrane, in cm.

[0130] Tensile strength refers to the ratio of the maximum tensile force to the cross section of the sample during the tensile test. The tensile strength and elongation are measured in accordance with the determination method of plastic film GB / T1040.3 2006.

[0131] The measured results are shown in Table 1.

[0132] Table 1

[0133]

[0134] It can be seen from the results in Table 1 that the performance of all the embodiments of the present invention is better than that of the comparative examples.

[0135] By comparing the various embodiments, it can be seen that when the ratio of 100 nm small-particle LLZO to 1 μm large-particle LLZO is 1:1.5-2 (preferably 3:5), the ionic conductivity and tensile strength of the composite electrolyte membrane are the highest.

[0136] By comparing Example 1 with Examples 4-5, it can be seen that when PEO or PTFE is used alone as a binder, the performance of the composite electrolyte membrane will decrease to varying degrees, so it is preferred to use PEO and PTFE at the same time.

[0137] By comparing Example 1 with Example 6, it can be seen that when PEO with a higher molecular weight is selected, the performance of the obtained composite electrolyte membrane is better.

[0138] By comparing Example 1 with Examples 9-10, it can be seen that the contents of SA and PTFE need to be controlled within a certain range, otherwise the performance of the composite electrolyte membrane will be adversely affected. In summary, Example 1 has the best comprehensive performance.

Claims

1. A composite electrolyte membrane, characterized in that: The composite electrolyte membrane comprises a lithium salt, a first oxide electrolyte, a second oxide electrolyte, stearic acid, optionally polyethylene oxide, optionally polytetrafluoroethylene and optionally a plasticizer; Wherein, the D 50 The second oxide electrolyte has a D of 10-200 nm. 50 The thickness of the first oxide electrolyte is 500 nm-5 μm, and the weight ratio of the first oxide electrolyte to the second oxide electrolyte is 1:1-3, preferably 1:1.5-2; The molecular weight of the polyethylene oxide is 5 million or more.

2. The composite electrolyte membrane according to claim 1, wherein: The D of the first oxide electrolyte 50 50-150nm, the D of the second oxide electrolyte 50 600nm-2μm.

3. The composite electrolyte membrane according to claim 1, wherein: The first oxide electrolyte and the second oxide electrolyte are each independently selected from one or more of lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum titanium oxide, and lithium germanium aluminum phosphate; more preferably, the first oxide electrolyte and the second oxide electrolyte each independently also contain one or more doping elements selected from aluminum, gallium, and tantalum.

4. The composite electrolyte membrane according to any one of claims 1 to 3, wherein: The lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB).

5. The composite electrolyte membrane according to any one of claims 1 to 4, wherein: The molecular weight of the polyethylene oxide is 6 million to 8 million; preferably, the polytetrafluoroethylene is dispersed polytetrafluoroethylene.

6. The composite electrolyte membrane according to any one of claims 1 to 5, wherein: The total weight of the first oxide electrolyte and the second oxide electrolyte accounts for 50-98%, preferably 60-90%, of the total weight of the composite electrolyte membrane; Preferably, the weight of the lithium salt accounts for 1-10%, preferably 2-7%, relative to the total weight of the composite electrolyte membrane; Preferably, relative to the total weight of the composite electrolyte membrane, the weight of stearic acid is 0.1-2%, preferably 0.2-1%; and / or the weight of polyethylene oxide is 0-10%, preferably 1-10%, more preferably 2-6%; and / or the weight of polytetrafluoroethylene is 0-5%, preferably 0.1-5%, more preferably 0.2-1%.

7. A method for preparing a composite electrolyte membrane, characterized in that: The preparation method comprises: pressurizing and molding the electrolyte mixture to obtain a composite electrolyte membrane; The electrolyte mixture contains a lithium salt, a first oxide electrolyte, a second oxide electrolyte, stearic acid, optionally polyethylene oxide, optionally polytetrafluoroethylene, and optionally a plasticizer; The D of the first oxide electrolyte 50 The second oxide electrolyte has a D of 10-200 nm. 50 The thickness of the first oxide electrolyte is 500 nm-5 μm, and the weight ratio of the first oxide electrolyte to the second oxide electrolyte is 1:1-3, preferably 1:1.5-2; The molecular weight of the polyethylene oxide is 5 million or more.

8. The preparation method according to claim 7, wherein: The D of the first oxide electrolyte 50 50-150nm, the D of the second oxide electrolyte 50 600nm-2μm.

9. The preparation method according to claim 7 or 8, wherein: The first oxide electrolyte and the second oxide electrolyte are each independently selected from one or more of lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum titanium oxide, and lithium germanium aluminum phosphate; more preferably, the first oxide electrolyte and the second oxide electrolyte each independently also contain one or more doping elements selected from aluminum, gallium, and tantalum.

10. The preparation method according to any one of claims 7 to 9, wherein The lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB).

11. The preparation method according to any one of claims 7 to 10, wherein: The molecular weight of the polyethylene oxide is 6-8 million; Preferably, the polytetrafluoroethylene is dispersed polytetrafluoroethylene.

12. The preparation method according to any one of claims 7 to 11, wherein The total weight of the first oxide electrolyte and the second oxide electrolyte accounts for 50-98%, preferably 60-90%, of the total weight of the electrolyte mixture; Preferably, the weight of the lithium salt is 1-10%, preferably 2-7%, relative to the total weight of the electrolyte mixture; Preferably, relative to the total weight of the electrolyte mixture, the weight of stearic acid is 0.1-2%, preferably 0.2-1%; and / or the weight of polyethylene oxide is 0-10%, preferably 1-10%, more preferably 2-6%; and / or the weight of polytetrafluoroethylene is 0-5%, preferably 0.1-5%, more preferably 0.2-1%.

13. The preparation method according to any one of claims 7 to 12, wherein: The preparation method of the electrolyte mixture comprises the following steps: (1) performing a first mixing of a first oxide electrolyte, a second oxide electrolyte, and stearic acid to obtain a first mixture; (2) mixing the first mixture obtained in step (1) with a lithium salt and an optional plasticizer to obtain a second mixture; (3) performing a third mixing of the second mixture obtained in step (2) and optional polyethylene oxide to obtain a third mixture; (4) Optionally, the third mixture obtained in step (3) is mixed with polytetrafluoroethylene to obtain a fourth mixture; Preferably, the first mixing to the fourth mixing are all performed by grinding; More preferably, the grinding conditions include: a rotation speed of 5000 rpm or more, preferably 6000-10000 rpm; and a time of 2 min or more, preferably 2-10 min.

14. The preparation method according to any one of claims 6 to 11, wherein The conditions for the pressure molding include: a temperature of 20-80°C, preferably 50-80°C.

15. Use of the composite electrolyte membrane according to any one of claims 1 to 6 or the composite electrolyte membrane prepared by the preparation method according to any one of claims 7 to 14 in a lithium ion battery.